2020
DOI: 10.1101/2020.05.20.105775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UBTD1 regulates ceramide balance and endolysosomal positioning to coordinate EGFR signaling

Abstract: To adapt in an ever-changing environment, cells must integrate physical and chemical signals and translate them into biological meaningful information through complex signaling pathways. By combining lipidomic and proteomic approaches with functional analysis, we have shown that UBTD1 (Ubiquitin domain-containing protein 1) plays a crucial role in both the EGFR (Epidermal Growth Factor Receptor) self-phosphorylation and its lysosomal degradation. On the one hand, by modulating the cellular level of ceramides t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In addition, RNF26 depletion blocks EGF trafficking to the perinuclear cloud from the cell periphery, as well as EGFR degradation upon EGF engagement, and it redistributes the transferrin receptor (TfR) toward the cell periphery (Jongsma et al, 2016). Two subsequent studies have also indicated RNF26 facilitates the targeting of EGFR to the lysosome for degradation (Cremer et al, 2021;Torrino et al, 2021). We have shown that USP17 is required for clathrin-mediated endocytosis of EGFR and TfR, and that USP17 depletion also blocks EGFR degradation upon EGF engagement, although it blocks its endocytosis, rather than its subsequent targeting to the lysosome (Jaworski et al, 2014).…”
Section: Usp17 Deubiquitylates P62 and Opposes Rnf26 To Allow Lysosom...mentioning
confidence: 99%
“…In addition, RNF26 depletion blocks EGF trafficking to the perinuclear cloud from the cell periphery, as well as EGFR degradation upon EGF engagement, and it redistributes the transferrin receptor (TfR) toward the cell periphery (Jongsma et al, 2016). Two subsequent studies have also indicated RNF26 facilitates the targeting of EGFR to the lysosome for degradation (Cremer et al, 2021;Torrino et al, 2021). We have shown that USP17 is required for clathrin-mediated endocytosis of EGFR and TfR, and that USP17 depletion also blocks EGFR degradation upon EGF engagement, although it blocks its endocytosis, rather than its subsequent targeting to the lysosome (Jaworski et al, 2014).…”
Section: Usp17 Deubiquitylates P62 and Opposes Rnf26 To Allow Lysosom...mentioning
confidence: 99%